Preparation and Properties of Water-borne Zinc-rich Epoxy Primer - LI Shi-zheng, WANG De-xiu, LI Xin-xiong, LUO Xiao-hu, ZHU Ri-long, XIE Jia-wu, LI Ji, WU Da-wang, LIU Ya-li (Cailiao Baohu)
Based on the development of water-borne curing agent with excellent water dilubility, an environment-friendly two-component water-borne zinc-rich epoxy primer was studied.Firstly, zinc powder and the various additives were evenly dispersed in the water-based epoxy resin curing agent with ethanol as solvent to prepare stable curing agent.The stability of zinc powder in water-borne epoxy curing agent was studied by solvent precipitation rate test and high-speed centrifugation test.The effect of zinc powder content, particle size and shape on the film performance was studied by testing the anti-corrosion performance of the film.The water-borne epoxy zinc rich primer was characterized by scanning electron microscopy(SEM)and thermogravimetric analysis(TGA)to study the morphology and heat resistance.The results showed that the mechanical and anticorrosive properties of waterborne epoxy zinc rich primer are the best when the particle size of spherical and ellipsoidal mixed zinc powder is about 3.8 μm and the content of zinc powder is 75%～80%.